An hour before daylight : Memories of a rural boyhood - Carter, Jimmy (New York, NY Simon & Schuster, 2001)
The former president offers an account of growing up on a Georgia farm during the Depression and provides profiles of the people who shaped his life
D., 12/02
Keywords: Carter, Jimmy--Childhood and youth -- Biography; Presidents -- Biography -- United States; Farmers -- Biography -- Plains, GA; Plains (Ga.)--Social life and customs--20th century -- Biography